EFEKTIFITAS MODEL PEMBELAJARAN COOPERATIVE SCRIPT DALAM MENINGKATKAN KETERAMPILAN MEMBACA SISWA DALAM PELAJARAN BAHASA ARAB - Yumna Fatin Inayah; Muqimah Liwais Sunnah; Hafidz, Muhammad (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2025)
Cooperative script learning model is one of the cooperative learning that emphasizes the process of working together in groups to understand the script and present the message conveyed by the author. The objectives of this study is to determine the effectiveness of cooperative script learning model in improving the Arabic reading skills of students in class XI IPS MAN 1 Mojokerto. This type of research uses quantitative research with method pre-experiment (one group pretest posttest). The sample was obtained by random sampling technique, namely class XI IPS 3 MAN 1 Mojokerto which amounted to 34 students. Data collection techniques that researchers use are observation, interviews, documentation and tests. As for data analysis technique using validity tests, reliability tests, T tests, and N-Gain tests. Based on the results of the T test obtained is > . So it can be concluded that the cooperative script learning model is effective in improving students reading skills and after calculating the nomalized Ngain on the average pretest and posttest scores, Ngain was obtained at 71.938 (72%) with a fairly effective category. So it can be concluded that there is a great influence of the cooperative script learning model in improving students reading skills.